Positive electrode and lithium secondary battery containing the same

JP2026530394APending Publication Date: 2026-09-08LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026510817
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-27
Publication Date
2026-09-08

AI Technical Summary

Benefits of technology

【0025】 本発明による正極は、正極活物質粒子の表面に配置され、粒子と粒子と連結するカーボンナノチューブと、粒子と粒子との間に配置され、空隙上で電解液を保持するカーボンブラックの位置関係と連結性を改善することにより、カーボンナノチューブを介して導電ネットワークが緻密に形成され、且つ活物質粒子間の空隙では、カーボンブラックが電解液を保持しており、電気伝導性とイオン伝導性をいずれも向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026530394000001
    Figure 2026530394000001
  • Figure 2026530394000002
    Figure 2026530394000002
  • Figure 2026530394000003
    Figure 2026530394000003
Patent Text Reader

Abstract

The present invention relates to a positive electrode composite layer containing a positive electrode active material, carbon nanotubes, and carbon black, which is arranged on a current collector, and the BET specific surface area (BET) of the carbon nanotubes. CNT ) BET specific surface area of ​​carbon black (BET CB ) ratio ((BET CB ) / (BET CNT )) is greater than 1.0 and 3.4 or less, and the cumulative average particle size (D) of the carbon nanotubes 50 CNT This invention relates to a positive electrode characterized by having a size of 0.9 μm to 2.0 μm. The superior positional relationship between carbon nanotubes and carbon black within the positive electrode, as well as the excellent connectivity with active material particles, improves both ionic conductivity and electrical conductivity. As a result, it is possible to provide a lithium secondary battery with excellent resistance characteristics, improved lifespan, and price competitiveness.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a positive electrode for a lithium secondary battery and a lithium secondary battery containing the same, and more particularly to a positive electrode to which a conductive material optimized for ensuring conductivity is applied and a lithium secondary battery containing the same. [Background technology]

[0002] A lithium secondary battery generally consists of a positive electrode, a negative electrode, a separator, and an electrolyte, and the positive electrode and negative electrode contain an active material that allows for the insertion and deintercalation of lithium ions.

[0003] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMnO4, etc.), and lithium iron phosphate compounds (LiFePO4) have been used as positive electrode active materials for lithium secondary batteries. Of these, lithium cobalt oxide has the advantage of a high operating voltage and excellent capacity characteristics, but the high price of cobalt, the raw material, and its unstable supply make commercial application to high-capacity batteries difficult. Lithium nickel oxide has poor structural stability, making it difficult to achieve sufficient lifespan characteristics. On the other hand, lithium manganese oxide has excellent stability but suffers from poor capacity characteristics. Therefore, in order to complement the problems of lithium transition metal oxides containing Ni, Co, or Mn alone, lithium nickel-based oxides containing two or more transition metals have been developed, and among them, lithium nickel cobalt manganese oxide containing Ni, Co, and Mn is widely used in the field of electric vehicle batteries.

[0004] On the other hand, while applying a positive electrode active material with high capacity characteristics is important for manufacturing batteries with high energy density, the materials contained in the positive electrode also play a crucial role. For this reason, research is being conducted to maximize the proportion of active material and minimize the content of conductive material and binder. However, when the amount of active material used increases, the increase in the unit cost of the cell is very large compared to the degree of performance improvement, making it difficult to actually apply to mass production.

[0005] Therefore, the recent trend in research is to achieve a certain energy density while also increasing price competitiveness.

[0006] On the other hand, carbon nanotubes (CNTs) are often used as conductive materials for the positive electrode. This is because CNTs have superior conductivity and length characteristics compared to carbon black, making them advantageous for forming conductive networks. Among these, single-wall carbon nanotubes (SWCNTs) are advantageous for forming conductive networks, but they are not easy to disperse, are expensive, and despite their superior performance, they have a significant disadvantage in terms of price competitiveness. Multi-wall carbon nanotubes (MWCNTs) also have problems in terms of economic flexibility, and there is a problem of damage or fracture of the active material during electrode rolling.

[0007] Therefore, the present invention aims to provide a cathode composition that is competitive in terms of price and also superior in terms of performance compared to cells using CNTs as a conductive material. [Overview of the project] [Problems that the invention aims to solve]

[0008] The present invention aims to solve the above-mentioned problems and to provide a cathode that can improve both electrical conductivity and ionic conductivity by improving the positional relationship between carbon nanotubes and carbon black and the connectivity between particles.

[0009] Another object of the present invention is to provide a lithium secondary battery which is excellent in resistance characteristics, has an improved service life, and can secure price competitiveness by including the positive electrode. Means for Solving the Problem

[0010] [1] In order to solve the above problem, in one aspect of the present invention, a positive electrode mixture layer containing a positive electrode active material, carbon nanotubes and carbon black is disposed on a current collector, satisfies the following formula 1, and the cumulative number-average particle diameter of the carbon nanotubes (D 50 CNT ) is 0.9 μm to 4.0 μm is provided. [Formula 1] 1.0 < (BET CB ) / (BET CNT ) ≦ 3.4 In the above formula 1, BET CB is the BET specific surface area of carbon black (m 2 / g), and BET CNT is the BET specific surface area of carbon nanotubes (m 2 / g).

[0011] [2] In the positive electrode according to [1] above, (BET CB ) / (BET CNT ) may be from 1.1 to 3.0.

[0012] [3] In the positive electrode according to [1] and / or [2] above, the BET CB may be 110 m 2 / g to 350 m 2 / g.

[0013] [4] In at least one positive electrode among [1] to [3] above, the BET CNT may be 100 m 2 / g to 250 m 2 / g.

[0014] [5] In at least one of the positive electrodes from [1] to [4] above, the cumulative average particle size of the carbon black (D 50 CB The thickness may be 0.8 μm to 1.5 μm.

[0015] [6] In at least one of the cathodes from [1] to [5] above, the weight ratio of the carbon nanotube and carbon black may be 85:15 to 55:45.

[0016] [7] In at least one of the positive electrodes described in [1] to [6] above, the positive electrode active material is of the single-particle type and may include one or more selected from the group consisting of lithium nickel oxides and lithium metal phosphate compounds.

[0017] [8] In at least one of the positive electrodes from [1] to [7] above, the positive electrode active material is a single-particle type containing 30 or fewer nodules, and the average particle size of the nodules (D mean The particle size may be between 0.2 μm and 3.0 μm.

[0018] [9] In at least one of the positive electrodes from [1] to [8] above, the positive electrode active material is a single-particle type containing 30 or fewer nodules, and the average particle size (D mean ) for volume cumulative average particle size (D 50 The ratio of single-particle ratios (D 50 / D mean ) may be between 1 and 10.

[0019]

[10] In at least one of the positive electrodes from [1] to [9] above, the positive electrode active material comprises a single-particle lithium nickel oxide, and the single-particle lithium nickel oxide may have a composition represented by the following chemical formula 1. [Chemical formula 1] Li 1+x Ni a Co b M 1 c M 2 d O2-e X e In the above chemical formula 1, M 1 It includes one or more selected from Mn and Al, and M 2 x contains one or more elements selected from the group consisting of W, Zr, Y, Ba, Ca, Ti, V, Mg, Ta, and Nb, and X contains one or more elements selected from the group consisting of N, P, S, F, and Cl, with 0 ≤ x ≤ 0.1, 0.5 ≤ a < 1, 0 <b≦0.35、0<c≦0.35、0≦d≦0.05および0≦e≦0.05である。

[0020]

[11] In at least one of the positive electrodes from [1] to

[10] above, the positive electrode active material comprises a lithium metal phosphate compound, and the lithium metal phosphate compound may have a composition represented by the following chemical formula 2. [Chemical formula 2] Li 1+x [Fe 1-y M y ]PO4 In the above chemical formula 2, M comprises one or more elements selected from the group consisting of Mn, Co, Ni, Al, Mg, and Ti, and -0.5 ≤ x ≤ 0.5 and 0 ≤ y < 1.

[0021]

[12] In at least one of the cathodes from [1] to

[11] above, the total weight of the carbon nanotubes and carbon black may be 0.4% to 2.5% by weight of the total weight of the cathode composite layer.

[0022]

[13] In at least one of the positive electrodes from [1] to

[12] above, the positive electrode active material may be present in an amount of 93.0% to 99.0% by weight relative to the total weight of the positive electrode composite layer.

[0023]

[14] In at least one of the positive electrodes from [1] to

[13] above, the positive electrode composite layer may further include a binder.

[0024]

[15] In another aspect of the present invention, a lithium secondary battery is provided which includes at least one positive electrode from [1] to

[14] above. [Effects of the Invention]

[0025] The positive electrode according to the present invention improves the positional relationship and connectivity between carbon nanotubes, which are arranged on the surface of the positive electrode active material particles and connect the particles, and carbon black, which is arranged between the particles and holds the electrolyte in the voids. As a result, a dense conductive network is formed via the carbon nanotubes, and the carbon black holds the electrolyte in the voids between the active material particles, thereby improving both electrical conductivity and ionic conductivity.

[0026] Furthermore, by applying carbon nanotubes and carbon black having the above-described characteristics, the lithium secondary battery including the positive electrode can exhibit superior resistance characteristics, improved lifespan, and maintain price competitiveness. [Modes for carrying out the invention]

[0027] The terms and words used herein and in the claims should not be interpreted in a manner limited to their ordinary or dictionary meanings, but rather in a manner consistent with the technical idea of ​​the present invention, in accordance with the principle that inventors may define the concepts of terms as appropriate to best describe their invention.

[0028] In this specification, terms such as “includes,” “equip,” or “have” specify the presence of an implemented feature, figure, step, component, or combination thereof, and should be understood not to preclude the existence or possibility of adding one or more other features, figures, steps, components, or combinations thereof.

[0029] In this invention, "single-particle type" means a particle consisting of 30 or fewer nodules, and the concept of single-particle type particles includes single particles consisting of one nodule and pseudo-single particles which are composites of 2 to 30 nodules.

[0030] The aforementioned "nodule" is a lower particle unit that constitutes a single particle or a pseudo-single particle, and may be a single crystal without crystalline grain boundaries, or a polycrystalline material in which no grain boundaries appear to exist when observed with a scanning electron microscope at a field of view of 5,000 to 20,000 times magnification.

[0031] In this invention, "secondary particle" refers to a particle formed by the aggregation of several tens to hundreds of primary particles. More specifically, a secondary particle is an aggregate of 50 or more primary particles.

[0032] The term "particle" as used in this invention may include one or all of the following: single particles, pseudo-single particles, primary particles, nodules, and secondary particles.

[0033] In this invention, "average particle size of nodules (D mean The particle size of each nodule is determined for approximately 30 particles containing one or more nodules, after which the particle size is taken as an average value by scanning electron microscope (SEM) to image the positive electrode active material particles.

[0034] In this invention, "volume cumulative average particle size (D 50 )" refers to the particle size at the 50% reference level of the volume-cumulative particle size distribution of the positive electrode active material powder. The volume-cumulative average particle size D 50 This can be measured using the laser diffraction method. For example, after dispersing the positive electrode active material powder in a dispersion medium, the particle size can be measured by introducing it into a commercially available laser diffraction particle size analyzer, obtaining a volume-cumulative particle size distribution graph, and then determining the particle size corresponding to 50% of the volume-cumulative amount.

[0035] In this invention, "number cumulative average particle size (D 50 CNT , D 50 CB")" refers to the particle size at the 50% reference point of the cumulative particle size distribution of carbon nanotubes and carbon black. The cumulative average particle size can be measured using the laser diffraction method. For example, after dispersing conductive material powder in a dispersion medium, it can be introduced into a commercially available laser diffraction particle size analyzer, and after obtaining a cumulative particle size distribution graph excluding volume, the particle size corresponding to 50% of the cumulative volume can be determined.

[0036] In this invention, "specific surface area (m²) 2 The value of " / g)" was measured using the BET method, and specifically, it can be calculated from the amount of nitrogen gas adsorbed under liquid nitrogen temperature (77K) using the BELSORP-mini II manufactured by BEL Japan.

[0037] The present invention will be described in more detail below.

[0038] The positive electrode and lithium secondary battery according to the present invention include at least one of the configurations described below, and may include any combination of technically possible configurations from the following.

[0039] <Positive electrode> The positive electrode according to the present invention comprises a positive electrode composite layer containing a positive electrode active material, carbon nanotubes, and carbon black, which is arranged on a current collector and satisfies the following formula 1, wherein the cumulative average particle size (D) of the carbon nanotubes. 50 CNT It is characterized by having a diameter of 0.9 μm to 4.0 μm.

[0040] [Formula 1] 1.0<(BET CB ) / (BET CNT )≦3.4

[0041] In the above formula 1, BET CB The BET specific surface area (m²) of carbon black is 2 / g) and BET CNT The BET specific surface area (m²) of carbon nanotubes is 2It is / g).

[0042] [Equation 1: (BET-CB) / (BET-CNT)] According to one embodiment of the present invention, the positive electrode is characterized in that a positive electrode composite layer containing a positive electrode active material, a linear conductive material such as carbon nanotubes, and a point-shaped conductive material such as carbon black is arranged on a current collector, and the ratio of the specific surface area of ​​carbon black to the specific surface area of ​​carbon nanotubes represented by formula 1 is greater than 1.0 and less than or equal to 3.4.

[0043] Conventional electrodes most commonly use carbon black as a conductive material. However, with commonly used carbon black, it is difficult to ensure conductivity unless a certain amount is present, making it difficult to realize batteries with high energy density.

[0044] Therefore, methods have been considered to reduce the proportion of conductive material by substituting carbon black and increase the proportion of active material. However, electrodes manufactured using such methods are mostly difficult to apply to mass production because they reduce the price competitiveness of the battery. For example, in order to reduce the proportion of conductive material, carbon nanotubes are used as the conductive material. However, in order to ensure conductivity with a small amount of carbon nanotubes, it is necessary to use single-wall carbon nanotubes with a large specific surface area. Dispersing such single-wall carbon nanotubes is also difficult, which is the main reason for the reduced price competitiveness.

[0045] Therefore, the present inventors provide a cathode composite layer composition that maximizes the conductive performance of the conductive material, thereby achieving the effects of securing a conductive network and improving ionic conductivity with a small amount of conductive material, even without using single-wall carbon nanotubes.

[0046] According to one embodiment of the present invention, the specific surface area of ​​the carbon nanotube represented by formula 1 (BET CNT ) Specific surface area of ​​carbon black (BET CB) ratio ((BET CB ) / (BET CNT The characteristic is that the ratio is greater than 1.0 and less than or equal to 3.4. Typically, carbon nanotubes have a linear, one-dimensional structure with a relatively large specific surface area, while carbon black has a point-like, three-dimensional structure with a relatively small specific surface area.

[0047] When carbon nanotubes and carbon black are mixed, the number of carbon nanotubes is greater than that of carbon black for the same weight, which may prevent each of the two conductive materials from being positioned in the optimal location within the electrode. For example, carbon nanotubes must either connect the active materials or bond to the surface of the active materials, which are larger particles formed by the aggregation of smaller particles, and play a role in connecting the smaller particles. However, if there are many of them, the probability of them being placed in the gaps between the active materials increases, and they may not be able to perform their intended function. Furthermore, they may be relatively thin and long, and may be cut or damaged between charge and discharge, potentially causing an increase in resistance. In the case of carbon black, it is preferable for it to be placed in the gaps between the active materials or to function as a hub connecting carbon nanotubes, but there is a problem in that carbon nanotubes prevent it from being placed in the gaps and instead place it on the surface of the active materials, thus not being able to contribute much to improving conductivity.

[0048] In the case of a positive electrode according to one embodiment of the present invention, conversely, the specific surface area of ​​the carbon black is larger than the specific surface area of ​​the carbon nanotubes. When a conductive material is constructed in this manner, the carbon nanotubes have a relatively small specific surface area, which allows for a relatively large diameter and a relatively short length. As a result, when connecting active material particles to form a conductive network, even when rolled at high pressure, there is less risk of damage to the conductive network, and the ability to maintain inter-particle connectivity is strong. Furthermore, because the specific surface area of ​​the carbon black is relatively large, the probability of carbon black particles being positioned in the voids formed between active material particles can be increased. The large specific surface area also provides excellent ability to retain electrolyte, and it has the advantage of being able to perform the function of improving ion conductivity in empty spaces such as voids.

[0049] In other words, if the specific surface area of ​​carbon nanotubes is greater than that of carbon black, that is, if the ratio according to Equation 1 is 1 or less, the carbon nanotubes may interfere with the placement of carbon black in the voids between active material particles, potentially reducing ionic conductivity. Furthermore, the cohesive force of the carbon nanotubes may increase, making dispersion difficult and potentially leading to uneven distribution. Additionally, if the ratio according to Equation 1 exceeds 3.4, problems may arise where the carbon nanotubes cannot smoothly form conductive pathways. This can be understood as a situation where the specific surface area of ​​carbon black is high and the relative number of nanotubes is large. As a result, carbon black has lower purity compared to carbon nanotubes, potentially increasing the possibility of side reactions.

[0050] The ratio of specific surface area in the formula 1 derived in this way is preferably 1.1 or more, 1.2 or more, or 1.3 or more, and may also be 3.3 or less, 3.1 or less, 3.0 or less, 2.8 or less, 2.6 or less, or 2.4 or less.

[0051] [Conductive materials: carbon nanotubes and carbon black] According to one embodiment of the present invention, the carbon nanotube has a cumulative number average particle size (D50 CNT The carbon nanotube is characterized by having a particle size of 0.9 μm to 4.0 μm. Unlike the volume-cumulative average particle size, the number-cumulative average particle size of the carbon nanotubes is derived simply from the distribution of particle size by number, without considering its volume. By considering the BET ratio and the number-cumulative average particle size, the influence of the number of conductive material particles among the factors affecting electrode performance can be considered more accurately. As a result, the number-cumulative average particle size of the carbon nanotubes may preferably be 0.95 μm or more, 1.00 μm or more, 1.05 μm or more, 1.10 μm or more, or 1.15 μm or more, and may also be 3.70 μm or less, 3.40 μm or less, 3.00 μm or less, 2.50 μm or less, or 2.00 μm or less. When the above range is met, it is easy to place them in the voids within the positive electrode, and by reducing the porosity of the positive electrode, it can help to realize a high-energy-density electrode.

[0052] On the other hand, the carbon nanotubes may be single-walled carbon nanotubes, multi-walled carbon nanotubes, or mixtures thereof, and preferably multi-walled carbon nanotubes. However, as long as the ratio of specific surface area with carbon black, as described later, can be satisfied, the use of single-walled or mixed single-walled and multi-walled carbon nanotubes is not excluded.

[0053] Furthermore, according to one embodiment of the present invention, the BET specific surface area of ​​the carbon nanotube is 100 m 2 / g~300m 2 It may also be expressed as / g, which is measured by the BET method, and specifically can be calculated from the amount of nitrogen gas adsorbed under liquid nitrogen temperature (77K) using BELSORP-mino II manufactured by BEL Japan. Preferably, 130m 2 / g or more, 150m 2 / g or more, 160m 2 / g or more, 170m 2 / g or more, 180m 2 / g or more, or 185m2 It may be more than / g, and also 290m 2 / g or less, 280m 2 / g or less, 275m 2 / g or less, 270m 2 / g or less, or 265m 2 The value may be less than or equal to / g. When the above range is met, the positive electrode can have the ability to form a conductive network by linking active material particles, which can improve electrical conductivity and thereby contribute to improving resistance characteristics and lifetime characteristics.

[0054] Furthermore, the positive electrode according to one embodiment of the present invention includes carbon black as a point-like conductive material, and the carbon black may be one or more selected from the group consisting of acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black.

[0055] According to one embodiment of the present invention, the BET specific surface area of ​​the carbon black is 110 m². 2 / g~350m 2 It may also be expressed as / g, which is measured by the BET method, and specifically can be calculated from the amount of nitrogen gas adsorbed under liquid nitrogen temperature (77K) using BELSORP-mino II manufactured by BEL Japan. Preferably, 130m 2 / g or more, 150m 2 / g or more, 170m 2 / g or more, 200m 2 / g or more, 220m 2 / g or more, 240m 2 / g or more, 260m 2 / g or more, or 280m 2 It may be more than / g, and also 340m 2 / g or less, 330m 2 / g or less, 325m 2 / g or less, 320m 2 / g or less, 310m 2 / g or less, or 305m 2may be / g or less. When the above range is satisfied, the material may be easily arranged in the voids within the positive electrode, has sufficient ability to retain the electrolytic solution in the voids, and contributes to improving ionic conductivity, so that improvements in resistance characteristics and lifespan characteristics can be expected.

[0056] According to one embodiment of the present invention, the carbon black has a cumulative number average particle diameter (D 50 CB ) may be 0.2 μm to 1.2 μm, preferably 0.3 μm or more, 0.4 μm or more, 0.5 μm or more, or 0.6 μm or more, and may be 1.1 μm or less, 1.0 μm or less, or 0.9 μm or less. When the above range is satisfied, the carbon black is easily arranged in the voids within the positive electrode, and reducing the porosity of the positive electrode can contribute to achieving an electrode with high energy density.

[0057] According to one embodiment of the present invention, the weight ratio of the carbon nanotubes to the carbon black may be 85:15 to 55:45. The weight ratio of the added amount of the carbon nanotubes to the added amount of the carbon black can be independent of the specific surface area ratio represented by Formula 1 above, and when the above range is satisfied, both ionic conductivity and electrical conductivity can be ensured simultaneously, and the effects of improving resistance characteristics and improving lifespan characteristics can be achieved. Preferably, the weight ratio of the carbon nanotubes to the carbon black may be 80:20 or less, or 75:25 or less, and may be 60:40 or more, or 65:35 or more.

[0058] [Positive Electrode Active Material] According to one embodiment of the present invention, the positive electrode active material may be of a single-particle type. The positive electrode active material has a single-particle degree (D 50 / D mean) may be 1 to 10. Single-particle positive electrode active materials have higher particle strength compared to conventional secondary particle positive electrode active materials in which tens to hundreds of primary particles are aggregated, resulting in less particle cracking during rolling. Furthermore, in the case of the single-particle positive electrode active material according to the present invention, since the number of lower constituent elements (i.e., nodules) that make up the particle is small, there is less change due to volume expansion and contraction of the primary particles during charging and discharging, and as a result, the occurrence of cracks inside the particle is also significantly reduced.

[0059] A smaller degree of single-particle formation means that the number of nodules constituting the particle is smaller. Preferably, the degree of single-particle formation may be 1 to 8, 1 to 7, 1 to 6, or 1 to 5. When this range is met, the degree of particle fracture can be reduced, the rolling density can be improved, and improvements in both lifetime characteristics and energy density can be expected.

[0060] When the positive electrode active material is of the single-particle type, it is preferable because it allows for the arrangement of carbon black within the voids and the formation of a network with carbon nanotube particles, and the effects of the specific surface area ratio range can be realized.

[0061] Furthermore, unlike in the case of secondary particle morphology, since only a minute amount of fine particles are generated by the particle fracture phenomenon, carbon black can occupy almost all of the voids, and an improvement in ion conductivity can be expected by retaining the electrolyte.

[0062] Furthermore, in the case of single-particle type, the specific surface area is relatively small compared to secondary particles, so the conductive network spots that must be formed by carbon nanotubes may be unnecessary. As a result, it is thought that the performance that would be obtained by carbon nanotubes with a large specific surface area is not present, and there is an advantage in that the function can be maximized by using carbon nanotubes with the same specific surface area as in the present invention. Despite having a relatively small specific surface area, there is an advantage in that the effect of improving conductivity can be maximized by using only a small amount.

[0063] Therefore, the positive electrode active material according to an embodiment of the present invention is preferably of a single-particle type, and in the case of the single-particle type, the effect obtained by satisfying the specific surface area relationship of the two conductive materials defined by the above-described Formula 1 can produce greater synergy.

[0064] According to an embodiment of the present invention, the volume cumulative average particle diameter (D 50 ) may be 2.0 μm to 6.0 μm.

[0065] The positive electrode active material has an average particle diameter at 50% of the cumulative volume of particles of 2.0 μm to 6.0 μm, which may be preferably 2.3 μm or more, 2.5 μm or more, 2.7 μm or more, 3.0 μm or more, or 3.5 μm or more, and may be 6.0 μm or less, 5.8 μm or less, 5.5 μm or less, or 5.0 μm or less. The volume cumulative average particle diameter D 50 when satisfying the above range, has the advantage that the rolling density can be increased without damage to the active material particles.

[0066] According to an embodiment of the present invention, the positive electrode active material may contain 30 or less nodules, and the average particle diameter of the nodules (D mean ) may be 0.2 μm to 3.0 μm; the average particle diameter of the nodules may preferably be 0.5 μm or more, 0.7 μm or more, or 1.0 μm or more, and may be 2.8 μm or less, 2.5 μm or less, or 2.0 μm or less. When the above range is satisfied, the range of the single-particle degree can be satisfied, and the effect therefrom can be expected.

[0067] The positive electrode active material according to the present invention may comprise one or more selected from the group consisting of lithium nickel-based oxides and lithium metal phosphate-based compounds, and the lithium nickel-based oxide may have a composition represented by the following Chemical Formula 1.

[0068] [Chemical Formula 1] Li 1+x Ni a Co b M1 c M 2 d O 2-e X e

[0069] In the above chemical formula 1, M 1 It includes one or more selected from Mn and Al, and M 2 x contains one or more elements selected from the group consisting of W, Zr, Y, Ba, Ca, Ti, V, Mg, Ta, and Nb, and X contains one or more elements selected from the group consisting of N, P, S, F, and Cl, with 0 ≤ x ≤ 0.1, 0.5 ≤ a < 1, 0 <b≦0.35、0<c≦0.35、0≦d≦0.05および0≦e≦0.05である。

[0070] In the above chemical formula 1, M 1 is Mn, Al, or a combination thereof, preferably Mn or a combination of Mn and Al, M 2 This is one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, preferably one or more selected from the group consisting of Zr, Y, Mg, and Ti, and more preferably Zr, Y, or a combination thereof. 2 While elements are not essential, if present in appropriate amounts, they can promote grain growth during calcination or improve crystal structure stability. Furthermore, X is an anion substituted at the oxygen site and can include N, P, S, F, or Cl.

[0071] The aforementioned 1+x represents the molar ratio of lithium in the lithium nickel oxide, and may be 0≦x≦0.1, 0≦x≦0.08, 0≦x≦0.05, 0≦x≦0.03, or 0≦x≦0.02.

[0072] The above a represents the molar ratio of nickel among the total metals other than lithium in the lithium nickel oxide, and may be 0.50≦a<1.00, 0.60≦a≦0.99, 0.70≦a≦0.99, 0.75≦a≦0.99, 0.80≦a≦0.99, 0.82≦a≦0.99, 0.84≦a≦0.99, or 0.86≦a≦0.99.

[0073] The above b represents the molar ratio of cobalt among the total metals other than lithium in the lithium nickel oxide, and 0 <b≦0.35、0.01≦b≦0.34、0.01≦b≦0.30、0.01≦b≦0.25、0.01≦b≦0.20、または0.01≦b≦0.15であってもよい。

[0074] The aforementioned c is M, which is the total metal other than lithium in the lithium nickel oxide. 1 The molar ratio is shown, 0 <c≦0.35、0.01≦c≦0.34、0.01≦c≦0.30、0.01≦c≦0.25、0.01≦c≦0.20、または0.01≦c≦0.15であってもよい。

[0075] The above d is M, which is the total metal other than lithium in the lithium nickel oxide. 2 This indicates the molar ratio of the elements, and may be 0≦d≦0.05, 0≦d≦0.02, or 0≦d≦0.01.

[0076] The aforementioned e represents the molar ratio of element X among all nonmetals other than oxygen in the lithium nickel oxide, and may be 0 ≤ e ≤ 0.05, 0 ≤ e ≤ 0.02, or 0 ≤ e ≤ 0.01.

[0077] On the other hand, the lithium nickel oxide may further include a coating layer on the surface of the particles containing one or more coating elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, and S.

[0078] When a coating layer is present on the surface of lithium nickel oxide particles, the coating layer suppresses contact between the electrolyte and the lithium nickel oxide, thereby reducing the elution of transition metals and the generation of gases due to side reactions with the electrolyte.

[0079] Preferably, the coating layer may contain Co as a coating element. When a coating layer containing Co is formed on the surface of lithium nickel oxide particles in single-particle and / or pseudo-single-particle form, an effect of suppressing side reactions with the electrolyte, as well as an effect of improving output, can be obtained.

[0080] Furthermore, the lithium metal phosphate compound may have a composition represented by the following chemical formula 2.

[0081] [Chemical formula 2] Li 1+x [Fe 1-y M y ]PO4

[0082] In the above chemical formula 2, M comprises one or more elements selected from the group consisting of Mn, Co, Ni, Al, Mg, and Ti, and -0.5 ≤ x ≤ 0.5 and 0 ≤ y < 1.

[0083] The lithium metal phosphate compound can be doped with M. In this case, the lattice structure and distance within the olivine crystal structure, which is the crystalline structure, change, increasing the diffusivity of lithium ions, and as a result, the electrochemical properties of the battery containing the positive electrode active material can be improved.

[0084] The aforementioned x may be -0.5 to 0.5, preferably -0.3 or greater, -0.1 or greater, or 0 or greater, and may also be 0.5 or less, 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.

[0085] The aforementioned y may be 0 or greater, less than 1, and may be 0.90 or less, 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, 0.30 or less, 0.20 or less, 0.10 or less, or 0.05 or less.

[0086] The lithium metal phosphate compound may be, for example, LiFePO4.

[0087] The lithium metal phosphate compound according to the present invention may be in the form of a single particle consisting of only one primary particle, or in the form of amorphous secondary particles consisting of 2 to 50 primary particles. Furthermore, the lithium metal phosphate compound may contain an olivine structure, and more specifically, may consist solely of an olivine structure. The coating layer according to the present invention may be formed not only on the secondary particles but also on the primary particles. That is, the coating layer according to the present invention can be uniformly present on the surface of primary particles that exist inside the secondary particles.

[0088] The coating layer may include a carbon coating layer with a graphite structure, and the thickness of the coating layer may be 0.5 nm to 5 nm. When the thickness of the coating layer is within the above range, there is an advantage in that electrical conductivity is improved and the movement of lithium ions is not hindered. Specifically, the thickness of the coating layer may be 0.5 nm or more, 1.0 nm or more, 1.5 nm or more, 2.0 nm or more, 2.5 nm or more, or 3.0 nm or more, and may be 5.0 nm or less.

[0089] The coating layer may be uniformly coated on the surface of the lithium metal phosphate compound. That is, the coating layer may be in the form of a thin film. The coating layer can improve the ionic conductivity and electronic conductivity during charging and discharging of the battery containing the positive electrode active material. In addition to carbon, the coating layer may contain trace amounts of impurities such as nitrogen, oxygen, and hydrogen.

[0090] The coating layer may be present in an amount of 0.5% to 3% by weight relative to the total weight of the lithium metal phosphate compound, in order to improve electrical conductivity and not hinder the movement of lithium ions.

[0091] [Positive electrode and others] As described above, the positive electrode according to the present invention comprises a single-particle positive electrode active material and a point-like conductive material, and may further comprise a binder. The positive electrode active material, the point-like conductive material, and the binder constitute a positive electrode composite layer, and the positive electrode composite layer can be formed on a positive electrode current collector.

[0092] Here, the positive electrode active material may be included in an amount of 90% to 99% by weight, more specifically 93% or more by weight, 95% or more by weight, 96% or more by weight, or 97% or more by weight, with a content of 98.5% or less by weight, or 98% or less by weight, and when included within the above content range, it can exhibit excellent capacity characteristics.

[0093] Furthermore, the conductive material containing carbon nanotubes and carbon black can be included in an amount of 0.4% to 2.5% by weight relative to the total weight of the positive electrode composite layer, preferably 0.5% or more, 0.6% or more, or 0.7% or more by weight, or 2.4% or less by weight, 2.3% or less by weight, 2.2% or less by weight, 2.1% or less by weight, 2.0% or less by weight, 1.9% or less by weight, 1.8% or less by weight, 1.7% or less by weight, 1.6% or less by weight, or 1.5% or less by weight. Such conductive material content is due to the positive electrode according to one embodiment of the present invention containing single-particle lithium nickel oxide and containing carbon nanotubes and carbon black as conductive materials that satisfy the ratio of specific surface area, which means that even with such a small amount of conductive material, it may be possible to improve both ionic conductivity and electrical conductivity.

[0094] Furthermore, according to one embodiment of the present invention, the positive electrode may further contain a binder. The binder plays a role in improving the adhesion between positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and polymers in which the hydrogens of these are substituted with Li, Na, or Ca, or various copolymers thereof, of which one or more can be used. The binder may be present in an amount of 0.1% to 10% by weight relative to the total weight of the positive electrode composite layer, preferably 0.3% or more by weight, 0.5% or more by weight, 0.7% or more by weight, or 1.0% or more by weight, and may also be 9.0% or less by weight, 8.5% or less by weight, 8.0% or less by weight, 7.5% or less by weight, 7.0% or less by weight, or 6.5% or less by weight.

[0095] The positive electrode current collector is not particularly limited as long as it contains a highly conductive metal, allows for easy adhesion of the positive electrode composite layer, and is unreactive within the battery voltage range. Examples of materials that can be used for the positive electrode current collector include stainless steel, aluminum, nickel, titanium, heat-treated carbon, or aluminum or stainless steel with surface treatments such as carbon, nickel, titanium, or silver. Furthermore, the positive electrode current collector can typically have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on its surface to enhance the adhesion of the positive electrode active material. It can be used in various forms, such as films, sheets, foils, meshes, porous materials, foams, and nonwoven fabrics.

[0096] The positive electrode can be manufactured by a conventional method for manufacturing a positive electrode, except that the positive electrode active material powder is used. Specifically, the positive electrode slurry composition, which is prepared by dissolving or dispersing the positive electrode active material powder and, if necessary, a binder, a conductive material, and a dispersant in a solvent, is applied to a positive electrode current collector, followed by drying and rolling.

[0097] The solvent may be any solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, or water, and one or more of these can be used individually or in mixtures of two or more. The amount of solvent used should be sufficient to dissolve or disperse the positive electrode active material, conductive material, binder, and dispersant, taking into consideration the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that allows for excellent thickness uniformity when applied for the manufacture of the positive electrode.

[0098] Alternatively, the positive electrode can also be manufactured by casting the positive electrode slurry composition onto another support, peeling it off the support, and then laminating the resulting film onto the positive electrode current collector.

[0099] [Lithium-ion secondary battery] Next, the lithium secondary battery according to the present invention will be described. The lithium secondary battery according to the present invention includes the positive electrode of the present invention as described above.

[0100] The lithium secondary battery specifically includes a positive electrode, a negative electrode positioned opposite the positive electrode, and a separator and electrolyte interposed between the positive and negative electrodes. As the positive electrode is as described above, a detailed explanation will be omitted, and only the remaining components will be described in detail below.

[0101] Furthermore, the lithium secondary battery may selectively further include a battery container for housing the electrode assembly comprising the positive electrode, negative electrode, and separator, and a sealing member for sealing the battery container.

[0102] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode composite layer located on the negative electrode current collector.

[0103] The negative electrode current collector is not particularly limited as long as it does not cause chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, heat-treated carbon, copper or stainless steel with surface treatment using carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy can be used. The negative electrode current collector can usually have a thickness of 3 μm to 500 μm, preferably 300 μm or less, 200 μm or less, 100 μm or less, or 80 μm or less. Fine irregularities can also be formed on the surface of the current collector to strengthen the bonding force with the negative electrode active material. For example, it can be used in various forms such as film, sheet, foil, mesh, porous material, foam, and nonwoven fabric.

[0104] As the negative electrode active material, a compound capable of reversible intercalation and deintercalation of lithium can be used. Examples thereof include carbon materials such as artificial graphite, natural graphite, Kish graphite, pyrolytic carbon, meso-carbon microbeads, mesophase pitches, petroleum or coal tar pitch derived cokes, mesophase pitch based carbon fiber, graphitized carbon fiber, amorphous carbon, soft carbon, and hard carbon; (quasi-)metallic materials capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO b (0<b≦2), (quasi-)metal oxide materials capable of doping and undoping lithium such as SnO₂, vanadium oxide, and lithium vanadium oxide; heterogeneous composite materials such as Si-C composites or Sn-C composites; and metallic lithium thin films. Any one of these or a mixture of two or more thereof can be used.

[0105] Preferably, the negative electrode active material may include one or more selected from the group consisting of silicon-based active materials, carbon-based active materials, and silicon-carbon composite active materials. More preferably, the carbon-based active material may include one or more selected from the group consisting of artificial graphite, natural graphite, soft carbon, and hard carbon, and the silicon-based active material includes pure Si particles and / or SiO b (0<b≦2), and the silicon-carbon composite active material may include a Si-C composite. Further, as the negative electrode active material, a mixed active material obtained by mixing two or more of the above-mentioned substances may be applied.

[0106] The negative electrode active material can be present in an amount of 60% to 99% by weight relative to the total weight of the negative electrode composite layer, preferably 70% or more by weight, 80% or more by weight, 85% or more by weight, or 90% or more by weight, and may also be present in an amount of 98% or less by weight, 97% or less by weight, or 95% or less by weight.

[0107] The binder is a component that helps to bond the conductive material, active material, and current collector, and can usually be added in an amount of 0.1% to 10% by weight relative to the total weight of the negative electrode composite layer, and can be present in amounts of 0.2% or more by weight, 0.3% or more by weight, or 0.5% or more by weight, and can also be present in amounts of 8% or less by weight, or 5% or less by weight. Examples of such binders include one or more selected from the group consisting of styrene-butadiene copolymer, acrylate-styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, acrylonitrile-butadiene-styrene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene copolymer, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, and polyvinyl alcohol. In particular, it may contain one or more selected from the group consisting of styrene-butadiene copolymer, acrylate-styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, acrylonitrile-butadiene-styrene copolymer, carboxymethylcellulose, hydroxypropylmethylcellulose, hydroxypropylcellulose, diacetylcellulose, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylfuran, cyanoethyl polyvinyl alcohol, cyanoethylcellulose, and cyanoethylsucrose. Preferably, carboxymethylcellulose, hydroxypropylmethylcellulose, hydroxypropylcellulose, or mixtures thereof are used. The conductive material is a component for further improving the conductivity of the negative electrode active material and can be added in an amount of 10% by weight or less, preferably 5% by weight or less, 3% by weight or less, 2% by weight or less, or 1% by weight or less, relative to the total weight of the negative electrode composite layer, and may also be included in amounts of 0.01% by weight or more, 0.05% by weight or more, 0.08% by weight or more, 0.1% by weight or more, or 0.3% by weight or more.Such conductive materials are not particularly limited as long as they do not cause chemical changes in the battery and are conductive. Examples of usable conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0108] The negative electrode composite layer can be manufactured by applying a negative electrode slurry composition, which is prepared by dissolving or dispersing a negative electrode active material and, selectively, a binder and a conductive material in a solvent, onto a negative electrode current collector and then drying it, or by casting the negative electrode slurry composition onto another support, peeling it off the support, and then laminating the resulting film onto the negative electrode current collector.

[0109] In the lithium secondary battery described above, the separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Generally, any separator commonly used in lithium secondary batteries can be used without particular limitations, but those with low resistance to ion movement of the electrolyte and excellent electrolyte moisture absorption capacity are particularly preferred. Specifically, porous polymer films, such as those made from polyolefin polymers like ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or laminated structures of two or more layers thereof, can be used. Alternatively, ordinary porous nonwoven fabrics, such as those made from high-melting-point glass fibers or polyethylene terephthalate fibers, can also be used. Furthermore, coated separators containing ceramic components or polymeric substances can be used to ensure heat resistance or mechanical strength, and can be selectively used as single-layer or multi-layer structures.

[0110] Examples of electrolytes used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries.

[0111] The electrolyte may include an organic solvent and a lithium salt.

[0112] The aforementioned organic solvent can be used without particular limitations, as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the aforementioned organic solvents include ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (propylene Carbonate solvents such as carbonate (PC); alcoholic solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (where R is a linear, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, and can include a double-bonded aromatic ring or ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes can be used. Among these, carbonate solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) is more preferred.

[0113] The lithium salt can be used without particular limitations as long as it is a compound that can provide lithium ions for use in lithium secondary batteries. Specifically, the anion of the lithium salt is F - Cl - , Br - , I - NO3 - , N(CN)2 - BF4 - CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2) 2CH - , (SF5)3C - , (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N - The lithium salt may be at least one selected from the group consisting of the following, and the lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2, etc. The concentration of the lithium salt is preferably in the range of 0.1M to 2.0M. When the concentration of the lithium salt falls within this range, the electrolyte can exhibit excellent electrolyte performance because it has appropriate conductivity and viscosity, and lithium ions can move effectively.

[0114] In addition to the components of the electrolyte, the electrolyte may also contain one or more additives, such as haloalkylene carbonate compounds like difluoroethylene carbonate, pyridine, triethyl phosphite, triethyl alcoholamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphate triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salts, pyrrole, 2-methoxyethyl alcohol, or aluminum trichloride, for purposes such as improving battery life characteristics, suppressing battery capacity reduction, and improving battery discharge capacity. Here, the additive may be present in an amount of 0.1 to 5% by weight relative to the total weight of the electrolyte.

[0115] <Examples> Hereinafter, embodiments of the present invention will be described in detail so that they can be easily implemented by a person with ordinary skill in the art to which the present invention pertains. However, the present invention can be realized in various different forms and is not limited to the embodiments described herein.

[0116] Examples 1a-4a and Comparative Examples 1a-8a D 50 It is 3.91 μm, D mean As a single-particle lithium nickel oxide with a particle size of 2.05 μm, LiNi 0.6 Co 0.1 Mn 0.3 A material having an O2 composition was applied as the positive electrode active material, and carbon black and multi-walled carbon nanotubes (in a 3:7 weight ratio) having the properties described in Table 1 below were applied as conductive materials to produce the positive electrodes of Examples 1a to 4a and Comparative Examples 1a to 8a.

[0117] The positive electrode was prepared by mixing the lithium nickel oxide, the conductive material, and the PVDF binder in a weight ratio of 97.0:1.2:1.8, adding N-methylpyrrolidone solvent to achieve a solid content of 72%, and mixing in a homogenizer at 2,500 rpm for 1 hour to produce a positive electrode slurry. Subsequently, the slurry was applied to one surface of an aluminum current collector, dried at 130°C, and then rolled twice using a roll-to-roll rolling mill at a linear pressure of 2,000 kgf / cm to produce the positive electrode slurry.

[0118] [Table 1]

[0119] Examples 1b-4b and Comparative Examples 1b-8b As single-particle lithium iron phosphate, D 50 is 1.1 μm, D mean A LiFePO4 composition with a particle size of 0.2 μm was used as the positive electrode active material, and carbon black and carbon nanotubes (in a weight ratio of 3:7) having the properties described in Table 2 below were used as conductive materials to produce the positive electrodes of Examples 1b to 4b and Comparative Examples 1b to 8b.

[0120] The positive electrode was manufactured by mixing the positive electrode active material, carbon black, and PVDF binder in an N-methylpyrrolidone solvent in a weight ratio of 97.0:1.2:1.8 to produce a positive electrode slurry (15,000 mPa.s), which was then applied to one surface of an aluminum current collector, dried at 130°C, and rolled at a linear pressure of 2,000 kgf / cm.

[0121] [Table 2]

[0122] 1) D mean The particle size (μm) was calculated by scanning electron microscopy (SEM) images of positive electrode active material particles at a magnification of 5.0 K, determining the particle size of each nodule for approximately 30 particles containing one or more nodules, and then taking the average value.

[0123] 2) Volume cumulative average particle diameter D 50 The particle size (μm) was determined by dispersing the sample powder in a dispersion medium, introducing it into a laser diffraction particle size analyzer (Mastersizer 3000, Malvern), obtaining a volume-cumulative particle size distribution graph, and then determining the particle size corresponding to 50% of the volume-cumulative amount.

[0124] 3) Number cumulative average particle diameter (μm) D 50 CNT and D 50 CB In this study, carbon nanotube and carbon black powders were dispersed in a dispersion medium, then introduced into a laser diffraction particle size analyzer (Mastersizer 3000, Malvern). After obtaining a cumulative particle size distribution graph excluding volume, the particle size corresponding to 50% of the cumulative particle size was determined.

[0125] 4) Specific surface area (m 2 The amount ( / g) was measured using the BET method and calculated from the amount of nitrogen gas adsorbed under liquid nitrogen temperature (77K) using a BELSORP-mino II manufactured by BEL Japan.

[0126] <Experimental Example 1: Evaluation of Resistive Characteristics> Artificial graphite was used as the negative electrode active material. A negative electrode was prepared containing a negative electrode composite layer with the negative electrode active material, CMC and SBR as negative electrode binders, and carbon black as a negative electrode conductive material in a weight ratio of 95.6:1.1:2.3:1.0. The weight loading amount of the negative electrode composite layer was 265.8 mg / 25 cm 2 The thickness was 78.5 μm, and a 10 μm thick copper foil was used as the negative electrode current collector.

[0127] The positive electrode, negative electrode, and porous polyethylene separator of the examples and comparative examples were assembled using a winding method. An electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio) and lithium hexafluorophosphate (LiPF 61 mol)) was injected into the assembled battery to manufacture a lithium secondary battery.

[0128] The lithium secondary battery was charged at a rate of 0.1 CC to 4.2 V, and then discharged to 2.5 V to perform an activation process.

[0129] After charging and discharging the lithium secondary battery, and after fully charging, while discharging, a 2.5C pulse current was applied for a specific time according to the change in State of Charge (SOC), and the surface resistance (0.1-second resistance), charge transfer resistance (0.1-30 second resistance), and diffusion resistance (30 second resistance) were measured. The results are shown in Tables 3 and 4.

[0130] <Experimental Example 2: Evaluation of Lifetime Characteristics> Each lithium secondary battery manufactured in Experimental Example 1 was charged in CCCV mode to 0.2C and 4.25V (termination current 1 / 20C). Subsequently, at 45°C, it was charged to 4.25V with a constant current of 0.33C and discharged to 2.5V with a constant current of 0.33C, with each cycle being performed. Resistance (DCIR) and charge / discharge capacity were measured while performing 100 charge / discharge cycles. Using the measurement results, the resistance increase rate and capacity retention rate were calculated as follows and are shown in Tables 3 and 4 below.

[0131] Resistance increase rate (%) = {(Resistance after 100 cycles) / (Resistance after 1 cycle) × 100} - 100

[0132] Capacity retention rate (%) = (Discharge capacity after 100 cycles) / (Discharge capacity after 1 cycle) × 100

[0133] [Table 3]

[0134] [Table 4]

[0135] Referring to Table 3 above, it can be seen that in Examples 1a to 4a, where positive electrodes with appropriately controlled conductive material properties are applied, not only is the capacitance retention rate low, but the initial resistance is also low, and the degree of resistance increase with the progression of the cycle is also low, confirming excellent performance. However, in Comparative Examples 1a to 8a, the lifespan is rapidly shortened, the electrode deteriorates quickly, the resistance increase rate is higher compared to the examples, and it can be seen that the performance is low.

[0136] Specifically, in Comparative Example 1a, the BET ratio is less than 1, and the poor result is due to the BET specific surface area of ​​carbon nanotubes being even larger than the BET specific surface area of ​​carbon black. It can be confirmed that the BET of carbon black is too low, resulting in a small number of particles for the same weight, which is inconvenient for the formation of conductive pathways. In the case of Comparative Example 2a, conversely, the BET of carbon black is too high, resulting in a BET ratio exceeding 3.4, which leads to a large number of particles. As a result, the side reactions have an adverse effect that exceeds the degree of performance improvement, and it can be confirmed that not only the lifespan but also the initial resistance is particularly poor compared to the example.

[0137] Furthermore, in the case of Comparative Example 3a, the cumulative average particle size of the carbon nanotubes was smaller than 0.9 μm, confirming that the formation of long conductive network connecting paths was not well achieved. In the case of Comparative Example 4a, the specific surface area of ​​the multi-wall carbon nanotubes was too large, effectively reaching the level of single-wall carbon nanotubes. This resulted in poor dispersibility due to the very strong cohesive force, preventing uniform distribution within the electrode and thus preventing the proper formation of conductive paths.

[0138] Furthermore, Comparative Examples 5a and 6a, which contain only carbon black, show that conductive pathways are not properly formed, resulting in poor resistance characteristics and a short lifespan, clearly demonstrating the problems with carbon black conductive materials. In addition, Comparative Examples 7a and 8a are examples using carbon nanotubes alone, and while they are considerably less cost-competitive than the Examples, they cannot fill the gaps between active material particles via carbon black, resulting in poor conductive pathway formation, and thus their resistance characteristics and lifespan characteristics are relatively inferior to the Examples.

[0139] Furthermore, looking at Examples 1b-4b and Comparative Examples 1b-8b in Table 4, which show the results of tests conducted with lithium iron phosphate as the active material, we can confirm that the results and trends are almost the same as those in Table 3. This indicates that controlling the type and properties of the conductive material to satisfy the ratio of the specific surface area of ​​carbon nanotubes to carbon black can greatly contribute to the formation of conductive pathways.

Claims

1. A positive electrode composite layer containing positive electrode active material, carbon nanotubes, and carbon black is placed on the current collector. The following equation 1 is satisfied, The cumulative average particle size (D) of the carbon nanotubes 50 CNT The positive electrode has a diameter of 0.9 μm to 4.0 μm. [Formula 1] 1.0<(BET CB ) / (BET CNT )≦3.4 In the above formula 1, BET CB The BET specific surface area (m²) of carbon black is 2 / g) and BET CNT The BET specific surface area (m²) of carbon nanotubes is 2 It is / g).

2. The (BET of Formula 1 CB ) / (BET CNT ) is 1.1 to 3.0, the positive electrode according to claim 1.

3. The aforementioned BET CB It is 110m 2 / g to 350m 2 The positive electrode according to claim 1, wherein the value is / g.

4. The aforementioned BET CNT is 100m 2 / g to 300m 2 The positive electrode according to claim 1, wherein the value is / g.

5. The cumulative average particle size (D) of the carbon black 50 CB The positive electrode according to claim 1, wherein the diameter is 0.2 μm to 1.2 μm.

6. The positive electrode according to claim 1, wherein the weight ratio of the carbon nanotubes and carbon black is 85:15 to 55:

45.

7. The positive electrode active material is of the single-particle type, The positive electrode according to claim 1, wherein the positive electrode active material comprises one or more selected from the group consisting of lithium nickel oxides and lithium metal phosphate compounds.

8. The positive electrode active material is a single-particle type containing 30 or fewer nodules. The average particle size (D) of the nodule mean The positive electrode according to claim 1, wherein the thickness of the ) is 0.2 μm to 3.0 μm.

9. The positive electrode active material is a single-particle type containing 30 or fewer nodules. The average particle size (D) of the nodule mean ) for volume cumulative average particle size (D 50 The single-particle ratio (D) is the ratio of ) 50 / D mean The positive electrode according to claim 1, wherein the value of ) is 1 to 10.

10. The positive electrode active material includes a single-particle lithium nickel oxide, The positive electrode according to claim 1, wherein the single-particle lithium nickel oxide has a composition represented by the following chemical formula 1. [Chemical formula 1] Li 1+x Ni a Co b M 1 c M 2 d O 2-e X e In the above chemical formula 1, M 1 It includes one or more selected from Mn and Al, M 2 x includes one or more elements selected from the group consisting of W, Zr, Y, Ba, Ca, Ti, V, Mg, Ta, and Nb, and x includes one or more elements selected from the group consisting of N, P, S, F, and Cl, with 0 ≤ x ≤ 0.1, 0.5 ≤ a < 1, 0 < b ≤ 0.35, 0 < c ≤ 0.35, 0 ≤ d ≤ 0.05, and 0 ≤ e ≤ 0.

05.

11. The positive electrode active material includes a lithium metal phosphate compound. The positive electrode according to claim 1, wherein the lithium metal phosphate compound has a composition represented by the following chemical formula 2. [Chemical formula 2] Li 1+x [Fe 1-y M y ]PO 4 In the above chemical formula 2, M comprises one or more elements selected from the group consisting of Mn, Co, Ni, Al, Mg, and Ti, and -0.5 ≤ x ≤ 0.5 and 0 ≤ y < 1.

12. The positive electrode according to claim 1, wherein the total weight of the carbon nanotubes and carbon black is 0.4% to 2.5% by weight of the total weight of the positive electrode composite layer.

13. The positive electrode according to claim 1, wherein the positive electrode active material is present in an amount of 93.0% to 99.0% by weight relative to the total weight of the positive electrode composite layer.

14. The positive electrode according to claim 1, wherein the positive electrode composite layer further comprises a binder.

15. A lithium secondary battery comprising the positive electrode described in claim 1.